Research on cryptographic properties of a new S-box based on cellular automaton - Jie GUAN; Junjun HUANG (Tongxin xuebao)
A new S-box based on cellular automata was found by experiments.The permutation properties of the S-box were analyzed,which proved that the S-box was a permutation only when the size of lattice was 5.Then the relation between the nontrivial difference transition probability of the S-box and the rank of the difference matrix was proved by constructing the difference matrix.And it was proved that the cyclic shift of input differential would not change the corresponding nontrivial differential transition probability,and obtained the sufficient and necessary conditions about the maximum and minimum nontrivial differential transition probabilities when the size of lattice was 5.Then the problem of the difference distribution of the S-box in this situation is completely solved.